1998
DOI: 10.1046/j.1365-201x.1998.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Myosin phosphatase: subunits and interactions

Abstract: Myosin phosphorylation is an important mechanism in regulating contractile activity of smooth muscle. The level of myosin phosphorylation depends on the balance of two enzymes, myosin light chain kinase and myosin phosphatase. Recently it has been discovered that myosin phosphatase can be regulated and this renewed interest in characterization of the phosphatase. It is suggested that the myosin phosphatase is composed of three subunits: a catalytic subunit of type 1 phosphatase (delta isoform; PP1c delta); and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 63 publications
1
75
0
Order By: Relevance
“…ROCK also inhibits myosin phosphatase by phosphorylation of its myosin-binding subunit (MBS; also named MYPT1) at Thr-853 and Thr-695 (numbers based on human sequence) (42)(43)(44)(45). Therefore, ROCK promotes MLC phosphorylation by direct phosphorylation and by inactivation of myosin phosphatase (46,47). We have recently found that ppMLC T18/S19 , pMLC S19 , and phosphorylation of MBS at Thr-853 (pMBS T853 ) are dependent on Rho and ROCK in human fibroblasts.…”
Section: Fibronectin (Fn)mentioning
confidence: 99%
“…ROCK also inhibits myosin phosphatase by phosphorylation of its myosin-binding subunit (MBS; also named MYPT1) at Thr-853 and Thr-695 (numbers based on human sequence) (42)(43)(44)(45). Therefore, ROCK promotes MLC phosphorylation by direct phosphorylation and by inactivation of myosin phosphatase (46,47). We have recently found that ppMLC T18/S19 , pMLC S19 , and phosphorylation of MBS at Thr-853 (pMBS T853 ) are dependent on Rho and ROCK in human fibroblasts.…”
Section: Fibronectin (Fn)mentioning
confidence: 99%
“…21 One possibility, suggested by Gong et al, 28 is that the gizzard MP was dissociated by arachidonic acid release. As pointed out previously, 29 an attractive feature of this idea is the precedent involving dissociation and regulation of glycogen-associated phosphatase after phosphorylation by PKA. 30 It is not known if PGF2␣ induces an increase in arachidonic acid, but the results of Gong et al 28 offer an interesting option for dissociation of MP in ferret portal vein cells.…”
Section: Shin Et Al Myosin Phosphatase Subunit Localization 551mentioning
confidence: 99%
“…One such mechanism is via phosphorylation of MYPT1 at an inhibitory site, ie, T695 in the larger chicken gizzard isoform. 29 This originated with the observation of Trinkle-Mulcahy et al 31 that incubation of permeabilized rabbit portal vein strips with ATP␥S caused thiophosphorylation of MYPT1 and inhibition of MP activity. Subsequently, it was found that a kinase(s) that co-purified with the MP preparations also phosphorylated MYPT1 at T695 and inhibited phosphatase activity.…”
Section: Shin Et Al Myosin Phosphatase Subunit Localization 551mentioning
confidence: 99%
“…With respect to the portal vein, the rightward shift in the isoproterenolinduced relaxation in I-1 (_/_) tissues suggests that I-1 may serve as a fine-tuning mechanism in regulating contractility in response to b-adrenergic agonists. The difference between the PKA effects of I-1 protein ablation in aorta and portal vein may reflect inherent differences in the myosin-targeting subunits or catalytic subunits themselves in each tissue (Hartshorne, 1998;Hartshorne et al 1998). In the light of the significant amount of I-1 present, other functions for I-1 in vascular smooth muscle are a strong possibility, but remain elusive.…”
Section: Protein Phosphatase Inhibitor-1 In Smooth Muscle Functionmentioning
confidence: 99%